The Condition and Direction of the Transport Infrastructure in Poland - Musiał-Malagó, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
An essential factor in speeding up an economy’s development and raising its competitiveness is improving the condition of its transport infrastructure, which should be modernised and expanded to strengthen the social and economic cohesion of the country. The current development level and technical condition of Poland’s transport infrastructure is a main barrier to economic growth and modernisation of the country and is hampering the country’s integration with the EU in the area of transport policy. The article presents the condition and development prospects for Poland’s transport infrastructure in the years 2000-2010 with a particular focus on road, rail and air transport. The article also shows the financial opportunities in developing the country’s transport infrastructure that have been created by EU regional policy. The deeper analysis covers the distribution and size of allocations predicted for the transport infrastructure in regional operating programmes for the years 2007-2013.